Implementation Of Combinatorial in Determining Password Technology - Fanny Ramadhani; Elza Ahmad; M. Fahri Fahroza; Ayu Syahfitri; Dimas Fadhlurohhman (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2021)
In the era of the Industrial Revolution 4.0, the use of technology has increased rapidly in less than 1 century, so that the use of technology has become a common need of society today. At this time, Users who use this technology even store personal or digitally important things such as storing important documents, personal information, even storing digital wallets or other things that are related to the user's confidentiality. so that to maintain the confidentiality of these things from other users, security is needed that can protect all the contents of the data that we have in this technology so that not just anyone can access things that are important in using this technology.